Photochemistry and Antioxidative Capacity of Female and Male Taxus baccata L. Acclimated to Different Nutritional Environments - Robakowski, Piotr; Pers-Kamczyc, Emilia; Ratajczak, Ewelina; Thomas, Peter A.; Ye, Zi-Piao; Rabska, Mariola; Iszkuło, Grzegorz (Frontiers in Plant Science, 2018)
In dioecious woody plants, females often make a greater reproductive effort than male individuals at the cost of lower growth rate. We hypothesized that a greater reproductive effort of female compared with male Taxus baccata individuals would be associated with lower female photochemical capacity and higher activity of antioxidant enzymes. Differences between the genders would change seasonally and would be more remarkable under nutrient deficiency. Electron transport rate (ETRmax), saturation photosynthetic photon flux corresponding to maximum electron transport rate (PPFsat), quantum yield of PSII photochemistry at PPFsat (PPFsat) and chlorophyll a fluorescence and activity of antioxidant enzymes were determined in needles of T. baccata female and male individuals growing in the experiment with or without fertilization. The effects of seasonal changes and fertilization treatment on photochemical parameters, photosynthetic pigments concentration and antioxidant enzymes were more pronounced than the effects of between-sexes differences in reproductive efforts. Results showed that photosynthetic capacity expressed as ETRmax and PPFsat and photosynthetic pigments concentrations decreased and non-photochemical quenching of fluorescence (NPQ) increased under nutrient deficiency. Fertilized individuals were less sensitive to photoinhibition than non-fertilized ones. T. baccata female and male individuals did not differ in photochemical capacity, but females showed higher maximum quantum yield of PSII photochemistry (Fv/Fm) than males. The activity of guaiacol peroxidase (POX) was also higher in female than in male needles. We concluded that larger T. baccata female reproductive effort compared with males was not at the cost of photochemical capacity, but to some extent it could be due to between-sexes differences in ability to protect the photosynthetic apparatus against photoinhibition with antioxidants.